ROLE OF STRESS MANAGEMENT STRATEGIES IN ENHANCING HEALTHCARE WORKERS PERFORMANCE: EVIDENCE FROM ASABA, DELTA STATE - Okonkwo, Joseph Emeka; Olannye, Peter A. (African Journal of Social and Behavioural Sciences, 2025)
The study examined the effect of stress management strategies on the performance of healthcare workers in Asaba Delta State. The study employed a cross-sectional survey research design. The population of the study was 211 employees of five selected private hospitals in Asaba, Delta State. Thus, 138 employees of the selected hospitals in Asaba, Delta State, were selected as the sample size. Stratified random sampling was used. The instrument’s reliability test was conducted using internal consistency. A structured questionnaire was used for data collection. The study employed multiple regression to test the stated hypotheses. The study revealed that relaxation techniques, exercise programs, mindfulness, and time management skills have a positive effect on the performance of healthcare workers. In conclusion, the integration of stress management strategies is vital for the well-being and performance of healthcare workers in Asaba, Delta State. The study recommended that hospital management should enhance its time management skills by prioritizing tasks, setting realistic goals, and using tools like planners or digital calendars.